2004
DOI: 10.1128/aac.48.5.1778-1787.2004
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Sphingolipid-Ergosterol Interactions Are Important Determinants of Multidrug Resistance in Candida albicans

Abstract: In this study, we examined the importance of membrane ergosterol and sphingolipids in the drug susceptibilities of Candida albicans. We used three independent methods to test the drug susceptibilities of erg mutant cells, which were defective in ergosterol biosynthesis. While spot and filter disk assays revealed that erg2 and erg16 mutant cells of C. albicans became hypersensitive to almost all of the drugs tested (i.e., 4-nitroquinoline oxide, terbinafine, o-phenanthroline, itraconazole, and ketoconazole), de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
155
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(162 citation statements)
references
References 51 publications
6
155
0
1
Order By: Relevance
“…We further confirmed this finding by assessing the ability of the Δcsn5 mutant to grow in the presence of nystatin and ketoconazole. Nystatin targets ergosterol in the cell membrane, while ketoconazole interferes with ergosterol biosynthesis [31]. As expected, the results shown in Table 4 indicate that Δcsn5 cells are indeed more sensitive to ketoconazole and more resistant to nystatin compared with the wild-type, again confirming an alteration in ergosterol biosynthesis.…”
Section: The δCsn5 Mutant Has Reduced Ergosterol Contentsupporting
confidence: 73%
“…We further confirmed this finding by assessing the ability of the Δcsn5 mutant to grow in the presence of nystatin and ketoconazole. Nystatin targets ergosterol in the cell membrane, while ketoconazole interferes with ergosterol biosynthesis [31]. As expected, the results shown in Table 4 indicate that Δcsn5 cells are indeed more sensitive to ketoconazole and more resistant to nystatin compared with the wild-type, again confirming an alteration in ergosterol biosynthesis.…”
Section: The δCsn5 Mutant Has Reduced Ergosterol Contentsupporting
confidence: 73%
“…An attractive model would be that Tac1p contributes to the raft association and proper routing of its target gene products Cdr1p, Cdr2p, and Rta3p to the plasma membrane by regulating AST2 expression. Recent studies have demonstrated that both sphingolipids and sterols are important determinants of surface localization of Cdr1p, as reduced membrane localization of Cdr1p was associated with increased susceptibility of C. albicans to ketoconazole in mutants defective in ergosterol biosynthesis (53). Interestingly, we found that Tac1p binding was enriched at the ERG1 (1.7-fold, P value of 0.0005) and ERG2 (1.6-fold, P value of 0.0011) promoters.…”
mentioning
confidence: 47%
“…Drug susceptibilities of yeast strains were measured by two independent methods: microdilution assay and spot assay. The MIC 80 s for the strains were determined with a broth microdilution method as described previously (11,16). For spot assay, 5-l samples of fivefold serial dilutions of each yeast culture (each with cells suspended in normal saline to an optical density at 600 nm of 0.1) were spotted onto YEPD plates in the absence (control) or in the presence of the drugs (11,16 …”
Section: Methodsmentioning
confidence: 99%
“…Current evidence suggests that Candida acquires azole resistance by employing multiple mechanisms that include (i) failure of drug accumulation mediated by extrusion pump proteins such as Cdr1p and Cdr2p, belonging to ATP binding cassette (ABC), and CaMdr1p, belonging to major facilitator superfamilies (MFS), (ii) alterations in the azole target protein Erg11p, and (iii) up regulation of the ERG11 gene (11,13,16).…”
mentioning
confidence: 99%